International orienteering experts' consensus on the definition, development, cause, impact and methods to reduce mental fatigue in orienteering: A Delphi study. Issue 23 (2nd December 2022) - Lam, Hui Kwan Nicholas; Sproule, John; Turner, Anthony P.; Murgatroyd, Paul; Gristwood, Graham; Richards, Hugh; Phillips, Shaun M.
ABSTRACT: Orienteering is an outdoor activity wherein participants use a map and compass to locate control points and choose the quickest path to the next control point in a natural environment. Attentional focus, rapid decision-making, and high aerobic fitness may influence orienteering performance. Therefore, this research aimed to seek international orienteering expert consensus regarding the definition, development, causes, influences and methods to reduce mental fatigue (MF) in orienteering based on practical experience. Following ethical approval, a three-round Delphi survey was conducted online with twenty-four orienteering coaches and athletes (or former athletes) from 10 different countries with international orienteering competition experience. The threshold of consensus was ≥ 70% agreement among respondents. The experts agreed that MF exists in daily life and orienteering with a substantial negative effect on their conscious decision-making performance and psychological responses. The experts disagreed that the form of MF that athletes experienced in orienteering training are similar to the competition. However, there was no agreement that MF would impact endurance and high-speed running performance during orienteering. This research refines the definition of MF and summarises the distinctions in what causes MF in orienteering training and competition, implying that MF should be addressed separately.